2017
DOI: 10.1007/s11695-016-2533-1
|View full text |Cite
|
Sign up to set email alerts
|

Milestone Weight Loss Goals (Weight Normalization and Remission of Obesity) after Gastric Bypass Surgery: Long-Term Results from the University of Michigan

Abstract: Background Rates of weight normalization and obesity remission after Roux-en-Y gastric bypass (GB) are unknown. This study evaluated weight loss, rates of achieving body mass index (BMI) < 25 or 30 kg/m2, recidivism, and predictors of success following GB. Methods We retrospectively studied weight and BMI at baseline, 2 and 6 months, and annually at 1–7 years in 219 patients undergoing GB at the University of Michigan from January 2008 to November 2010. Results Follow-up was excellent for a population trad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 29 publications
1
4
0
1
Order By: Relevance
“…However, among studies that reported postoperative BMI, mean or median BMIs were all above ‘normal’, and often ≥ 30, indicating that many participants would still be considered women in larger bodies [ 50 , 52 , 54 , 55 , 57 , 58 , 61 ]. This is consistent with previous research suggesting that the majority of patients do not achieve ‘normal’ BMI after bariatric surgery [ 85 , 86 ]. Nonetheless, future research should address weight loss and compare women in larger bodies within and across BMI categories to better understand how experiences with contraception may differ by body size, shape, or BMI classification.…”
Section: Discussionsupporting
confidence: 93%
“…However, among studies that reported postoperative BMI, mean or median BMIs were all above ‘normal’, and often ≥ 30, indicating that many participants would still be considered women in larger bodies [ 50 , 52 , 54 , 55 , 57 , 58 , 61 ]. This is consistent with previous research suggesting that the majority of patients do not achieve ‘normal’ BMI after bariatric surgery [ 85 , 86 ]. Nonetheless, future research should address weight loss and compare women in larger bodies within and across BMI categories to better understand how experiences with contraception may differ by body size, shape, or BMI classification.…”
Section: Discussionsupporting
confidence: 93%
“…We also report number of patients with more than 10 kg weight regain between 1 and 5 years16 and number of patients whose %EBMIL was below 50 at 5 years 17. Furthermore, we report number of patients whose BMI was below 30 kg/m 2 5 years after SG 18…”
Section: Methodsmentioning
confidence: 99%
“…LED cues in reward areas in both surgery groups. Since nonsurgical weight loss is often followed by weight regain, we expected that WL would show increased brain responsivity in reward areas vs. the surgery groups (Lager CJ et al, 2017;Sepulveda M et al, 2017). We also expected to see differences in connectivity between the RYGB and SG vs. WL and NT groups, given evidence that individuals with obesity have altered brain networks (Gupta A et al, 2015).…”
Section: Introductionmentioning
confidence: 99%